Oxford Clinical Psychology 2017
DOI: 10.1093/med-psych/9780195383706.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Treating Late Life Depression

Abstract: This workbook is designed for your use as you work together with a therapist to overcome your depression. It contains information on cognitive-behavioral therapy (CBT) and how it can help to reduce the symptoms of depression. Each chapter corresponds to a treatment module, and case examples are presented throughout and provide excellent illustrations of the main points, as well as summary questions, home assignments, and in-session exercises, worksheets, and forms. It explores how your thoughts, emotions, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies will be identified from the relevant domains of our evidence and gap map and screened against the eligibility criteria independently by two reviewers. Methods for study selection used to populate the evidence and gap map can be found in the protocol (Thompson-Coon, 2022).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Studies will be identified from the relevant domains of our evidence and gap map and screened against the eligibility criteria independently by two reviewers. Methods for study selection used to populate the evidence and gap map can be found in the protocol (Thompson-Coon, 2022).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Thus, older people who are more adept at emotional regulation and have a lifetime of experience of dealing with problems may make especially good candidates for CBT, and therapists working with older people are encouraged to maintain an optimistic expectation for change. There are a number of "how to" guides for applying CBT with older people, and interested readers are recommended to consult texts by Thompson et al (2010) and Laidlaw (2015).…”
Section: Normal Aging and Cbtmentioning
confidence: 99%